(untitled) (Bangladesh Journal of Botany, 2022)
Experiments were conducted to develop an efficient and reliable protocol for in vitro direct regeneration of potato for future transformation. Five varieties of potato viz. BARI Alu-7 (Diamant), BARI Alu-21 (Provento), BARI Alu-24 (Dura), BARI Alu-25 (Asterix) and BARI Alu-26 (Felsina); 3 levels of Zeatin riboside viz. 3, 4 and 5 mg/l ; 2 types of explants viz. internode and leaf from 19-22 days old micro plants were used in this study. Internode explants of BARI Alu-25 produced the highest number of shoots (40.17) within16 days without callus phase in MS medium supplemented with 5 mg/l ZR + 0.2 mg/l GA3 + 0.01 mg/l IAA followed by BARI Alu-21 (38.13), BARI Alu-7 (37.49), respectively. Leaf explants also produced shoots directly without callus phase in the same medium. In this case, the highest number (7.87) of shoots was found from the variety BARI Alu-25 followed by BARI Alu-21(7.42). ½MS medium supplemented with 0.5 – 1.0mg/l IBA resulted the best performance as to the rooting from ZR treated regenerated shoots having 100% plant survival at ex vitro conditions. This protocol may be used for rapid shoot proliferation and genetic transformation in potato. Bangladesh J. Bot. 51(4): 637-645, 2022 (December)